487 Reducing Intraoperative Fluoroscopic Radiation Exposure in Orthopaedic Theatres at A Trauma Centre. (4th May 2021) - Hayter, E; Rashid, M; Johnson, F; Erotocritou, M; Thomas, P
Abstract: Introduction: Intraoperative fluoroscopic imaging in orthopaedic trauma surgery subject's theatre staff and patients to increasing radiation exposure and its detrimental health effects. This audit cycle uses a target maximum for total number of intraoperative fluoroscopic images taken, as defined by recently published reference values, to reduce intraoperative radiation exposure. Method: This is a two-phase audit cycle retrospectively reviewing all trauma operations over a 12-month period (456 cases) and a 10-month period (256 cases) after disseminating the target standards through posters and focused training. Audit standards describe target maximum total intraoperative images taken for 5 commonly performed procedures, applicable to 33% of total cases. Operative notes, total intraoperative image count and radiation dose report were reviewed through ORMIS and PACS. Results: Audit standard compliance improved/remained at 100% in 4/5 of the investigated 'common procedures': from 2/5 procedures <80% compliance and 1/5 procedures =100% compliance initially, to 0/5 procedures <80% compliance and 2/5 procedures =100% compliance target upon re-audit. This translated to an improvement in mean radiation risk (DAP Gy.cm^2) in 3/4 common procedures (one exclusion due to dissimilar cohort characteristics). Conclusions: This study demonstrates employing a target maximum total image count limit reduced radiation exposure in trauma theatres.